Comportamiento de precios de mercados y análisis de volatilidad, para durazno (Prunus persica [L.] Batsch.) producido en Boyacá, Colombia - González González, Andrés; Puentes Montañez, Gloria Acened; Ruiz R., Edgar F. (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Páginas 48-62